Irisin, Energy Homeostasis and Male Reproduction - Sengupta, Pallav; Dutta, Sulagna; Karkada, Ivan Rolland; Akhigbe, Roland Eghoghosoa; Chinni, Suresh V. (Frontiers in Physiology, 2021)
Irisin, a novel skeletal muscle- and adipose tissue-secreted peptide, is a remarkable discovery by Boström and colleagues in the year 2012. It is conventionally regarded as an adipomyokine and is a cleaved fragment of Fibronectin type III domain-containing protein 5 (FNDC5). It is involved in the browning of white adipose tissue, glucose tolerance, and reversing of metabolic disruptions. Fertility is closely linked to energy metabolism and the endocrine function of the adipose tissue. Moreover, there is an established association between obesity and male infertility. Irisin bears strong therapeutic promise in obesity and its associated disorders, as well as shown to improve male reproductive functions. Thus, irisin is a molecule of great interest in exploring the amelioration of metabolic syndrome or obesity-induced male infertility. In this review, we aim to enumerate the most significant aspects of irisin actions and discuss its involvement in energy homeostasis and male reproduction. Though current and future research on irisin is very promiscuous, a number of clarifications are still needed to reveal its full potential as a significant medicinal target in several human diseases including male infertility.